Magnetotransport Properties in High-Quality Ultrathin Two-Dimensional Superconducting Mo2C Crystals - Wang, Libin; Xu, Chuan; Liu, Zhibo; Chen, Long; Ma, Xiuliang; Cheng, Hui-Ming; Ren, Wencai; Kang, Ning (ACS nano, 2016)
Ultrathin transition metal carbides are a class of developing two-dimensional (2D) materials with superconductivity and show great potentials for electrical energy storage and other applications. Here, we report low-temperature magnetotransport measurements on high-quality ultrathin 2D superconducting α-Mo2C crystals synthesized by a chemical vapor deposition method. The magnetoresistance curves exhibit reproducible oscillations at low magnetic fields for temperature far below the superconducting transition temperature of the crystals. We interpret the oscillatory magnetoresistance as a consequence of screening currents circling around the boundary of triangle-shaped terraces found on the surface of ultrathin Mo2C crystals. As the sample thickness decreases, the Mo2C crystals exhibit negative magnetoresistance deep in the superconducting transition regime, which reveals strong phase fluctuations of the superconducting order parameters associated with the superconductor–insulator transition. Our results demonstrate that the ultrathin superconducting Mo2C crystals provide an interesting system for studying rich transport phenomena in a 2D crystalline superconductor with enhanced quantum fluctuations.